2021
DOI: 10.1021/acsaelm.1c00236
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Dielectric Materials with Defect-Dipole Clusters Induced Colossal Permittivity and Ultra-low Loss

Abstract: Microwave dielectric materials are of great interest due to their applications in communication technology. The intrinsically low dielectric permittivity (generally less than 100) of traditional microwave dielectric materials has limited their capability in reducing the device size and developing various applications. In this paper, we report a microwave dielectric material, (La + Nb) co-doped BaSnO3, which exhibits both frequency- and temperature-independent colossal permittivity (ε > 103) over the frequency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…In the Nb + La co-doped BaSnO 3 system, due to the presence of dipole cluster defects, the huge dielectric constant remains almost unchanged over the entire measurement temperature range of 10-450 K. Even in the microwave frequency range (up to 1.8 GHz), its giant dielectric response remains. 45 Based on the previous discussion, it can be inferred that the sintered ceramic has a nonhomogeneous structure containing numerous point defects ((Ti ). They are entangled and combined to form defect clusters, which localize the delocalized electrons and reduce the loss due to electron conduction.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…In the Nb + La co-doped BaSnO 3 system, due to the presence of dipole cluster defects, the huge dielectric constant remains almost unchanged over the entire measurement temperature range of 10-450 K. Even in the microwave frequency range (up to 1.8 GHz), its giant dielectric response remains. 45 Based on the previous discussion, it can be inferred that the sintered ceramic has a nonhomogeneous structure containing numerous point defects ((Ti ). They are entangled and combined to form defect clusters, which localize the delocalized electrons and reduce the loss due to electron conduction.…”
Section: Resultsmentioning
confidence: 94%
“…This indicates that in the high‐frequency range (∼10 6 Hz), defect clusters are responsible for large ε r . In the Nb + La co‐doped BaSnO 3 system, due to the presence of dipole cluster defects, the huge dielectric constant remains almost unchanged over the entire measurement temperature range of 10–450 K. Even in the microwave frequency range (up to 1.8 GHz), its giant dielectric response remains 45 …”
Section: Resultsmentioning
confidence: 99%
“…What is more, the evolution of the defect-dipole polarization to the electric field is a linear relationship, which leads to an increased dielectric constant and obviously increased linear polarization behavior. Recently, La + Nb co-doped BaSnO 3 has effectively confirmed that a significant radius difference of dopants assisted the co-doping of each other in the system and formed defect-dipole clusters with large polarization, leading to colossal permittivity behavior similar to that observed in other co-doped systems. With this in mind, we take La and Mn co-doped PBLZST at A–B sites as an example, where La has a larger ion radius (117.2 pm) and Mn has a smaller radius (72 pm). According to the tolerant factor formula t = ( R A + R O )/(√2­( R B + R O )), in which the R A , R B , and R O are the radii of the ions of the ABO 3 structure, the t value of (Pb 0.9−Δ Ba 0.04 La 0.04+ x )­(Zr 0.65 Sn 0.3 Ti 0.05 Mn y )­O 3 is 0.859.…”
Section: Introductionmentioning
confidence: 85%
“…Therefore, the design and development of material systems with both high dielectric constant and low loss is a research hot spot in the field of dielectric materials. 17–20…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the design and development of material systems with both high dielectric constant and low loss is a research hot spot in the field of dielectric materials. [17][18][19][20] In 2013, a very promising candidate of donor and acceptor codoped rutile TiO 2 ceramics was found to possess unexpected ultrahigh permittivity and lower dielectric loss (e B 6 Â 10 4 , tan d o 0.05, 10 2 -10 6 Hz). 21 The author claims that the superior CP performance can be attributed to the electron-pinned defect dipole (EPDD) constructed by the diamond shape (Nb 2 5+ Ti 3+ A Ti , A = Ti 3+ /In 3+ /Ti 4+ ) and the triangular In 2 3þ V O Ti 3þ À Á coordination structure, which enable electrons to exist in the highly localized state.…”
Section: Introductionmentioning
confidence: 99%